THE UTILIZATION AND EFFECTIVENESS OF ESSENTIAL OIL FROM LEMONGRASS (Cymbopogon citratus) AS A SPRAY REPELLENT: PEMANFAATAN DAN EFEKTIVITAS MINYAK ATSIRI DARI BATANG SERAI (Cymbopogon citratus) SEBAGAI SPRAY REPELEN - Rina Kurniaty; Resmila Dewi; Erda Marniza (PT. ROCE WISDOM ACEH, 2024)
The lemongrass plant (Cymbopogon citratus) contains essential oil components consisting of 3 components, namely citronellal, citronellol, geraniol, and other components that are traditionally used as mosquito repellents. This study aims to utilize lemongrass stem essential oil in mosquito repellent preparations and find out at what concentration of lemongrass stem essential oil can be used as an anti-mosquito preparation. Essential oils are obtained using the steam distillation method. This research is experimental through laboratory testing. Three spray-repellent preparations were made with concentrations of 4%, 6%, and 8%. The tests carried out were organoleptic and preparation effectiveness tests against ten adult mosquitoes. The results of the study showed that spray repellents from lemongrass essential oil with concentrations of 4 and 6% were more effective in repelling and killing mosquitoes